Inquiry-Based Stress Reduction (IBSR) Technic As Psychological Intervention To Solve Student Stress In Learning Biology And Its Impact On Motivation, Knowledge Construction And Cognitive Anxiety - Saputri, Nova Vivi Clara; Rahmat, Adi; Hamdiyati, Yanti (Biosfer: Jurnal Pendidikan Biologi, 2024)
Learning difficulties are a common issue faced by students, with stress being a significant contributing factor.  One psychological treatment that has been shown to effectively reduce stress is Inquiry-Based Stress Reduction (IBSR). The objective of this study is to integrate IBSR into a discovery learning strategy in Biology in the classroom, with the aim of increasing students' learning motivation and knowledge construction while reducing their learning difficulties and cognitive anxiety. This is quasi-experimental research that used a post-test non-equivalent control group design. The study involved 72 11th-grade science students from two different classes at one of the public high schools in Bandung City. One class, consisting of 36 students, received IBSR treatment, while the other class, also consisting of 36 students, did not. Both classes used a discovery learning framework for teaching. Data on motivation, learning difficulties, and cognitive anxiety were collected using a rating scale questionnaire with eight scales. Students' ability to construct knowledge was measured using the German Cognitive Load (GCL) instrument in the form of a written test with indicators taken from Mayer's cognitive taxonomy (2002) in the realm of understanding. The study found that incorporating IBSR techniques into learning strategies for the immune system material can reduce student stress and improve learning performance, motivation, and knowledge construction (GCL), while also decreasing learning difficulties and cognitive anxiety.